(untitled) (Eureka Journal of Health Sciences & Medical Innovation, 2026)
This multidisciplinary methodological study synthesizes key psychological and pedagogical frameworks to enhance preventive care. Traditional medical education often prioritizes clinical expertise, leaving the physician’s role as a “motivator” and “social role model” insufficiently addressed. This gap frequently leads to low patient compliance and difficulties in implementing long-term lifestyle modifications. The study integrates James Prochaska’s Transtheoretical Model (TTM) for stage-matched interventions, Albert Bandura’s Self-Efficacy Theory to bolster patient confidence, and Daniel Goleman’s Emotional Intelligence (EQ) framework for empathetic rapport. Additionally, modern strategic instruments such as Gamification, Richard Thaler’s Nudge Theory, and Motivational Interviewing (MI) are analyzed as mechanisms for behavior modification. The integration of these multidisciplinary technologies allows healthcare professionals to transition from traditional clinical instructors to proactive “Health Ambassadors”. By utilizing personal role modeling and “choice architecture,” clinicians can trigger subconscious and voluntary patient engagement. The application of gamification elements (points, badges, leaderboards) and “nudge” interventions significantly improves adherence to healthy lifestyle (HLS) practices.